Enhancement of Heat Transfer by Ultrasound: Review and Recent Advances - Mathieu Legay; Nicolas Gondrexon; Stéphane Le Person; Primius Boldo; André Bontemps (International Journal of Chemical Engineering)
This paper summarizes some applications of ultrasonic vibrations regarding heat transfer enhancement techniques. Research literature is reviewed, with special attention to examples for which ultrasonic technology was used alongside a conventional heat transfer process in order to enhance it. In several industrial applications, the use of ultrasound is often a way to increase productivity in the process itself, but also to take advantage of various subsequent phenomena. The relevant example brought forward here concerns heat exchangers, where it was found that ultrasound not only increases heat transfer rates, but might also be a solution to fouling reduction.